The Routledge Encyclopedia of the Historical Jesus. - Evans, Craig A. (Taylor and Francis, 2014)
This Encyclopedia brings together the vast array of historical research into the reality of the man, the teachings, the acts, and the events ascribed to him that have served as the foundational story of one of the world's central religions. This kind of historiography is not biography. The historical study of the Jesus stories and the transmission of these stories through time have been of seminal importance to historians of religion. Critical historical examination has provided a way for scholars of Christianity for centuries to analyze the roots of legend and religion in a way th.